Sulfonated styrenic block copolymer membrane and energy storage device
By using lithium-ion battery separators with sulfonated styrene block copolymers as the separator material, the problems of chemical decomposition and low mechanical strength of traditional separators in alkaline electrolytes are solved, thereby achieving improved safety and high-efficiency electrochemical performance.
Patent Information
- Application Number
- CN202411231450.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-05
- Filing Date
- 2024-09-04
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional lithium-ion battery separators decompose chemically in alkaline electrolytes, have low mechanical strength and poor permeability resistance, and dendrite growth leads to safety issues.
Lithium-sulfonated styrene block copolymer (Li-SSBC) is used as the membrane material. By sulfonating styrene block copolymer (SSBC) and neutralizing it with lithium hydroxide to form Li-SSBC, the ion exchange capacity and conductivity of the material are improved, and the mechanical properties are enhanced.
It improves the mechanical strength and impermeability of the separator, enhances the safety and electrochemical performance of the battery, and ensures efficient ion conduction and electrolyte absorption.
Smart Images

Figure BDA0005026264740000021 
Figure BDA0005026264740000022 
Figure BDA0005026264740000091
Abstract
Description
Technical Field
[0001] The present invention relates to a lithiated-sulfonated styrene block copolymer composition, a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have made great progress in the application of portable electronics, electric vehicles and other large-scale energy storage fields. The separator is an indispensable component in lithium-ion batteries, which directly affects the electrochemical performance, especially safety. It is a key safety element to prevent battery short circuit. Rechargeable batteries must be equipped with safe separators.
[0003] The separator is a porous element, usually in the form of a thin film, that separates the chemical reactions of the anode and cathode in a battery. The separator can be applied directly as a coating to the anode and / or cathode. A self-supporting separator is not applied as a coating to one of the electrodes, but constitutes an independent component of the battery.
[0004] Conventional separators chemically decompose in alkaline electrolytes, which limits the battery life. In addition, some conventional separators exhibit low mechanical strength and poor permeation resistance due to dendrite growth.
[0005] Improved materials are needed to address some of the problems caused by conventional separators. A new styrenic block copolymer-based separator material with improved properties has been developed. SUMMARY OF THE INVENTION
[0006] One aspect of the present invention relates to a sulfonated styrenic block copolymer having a general configuration selected from the group consisting of: ACBA, ACBCA, ABCBA, (ACB) n A. (ABC) n A. (ACB) n X, (ABC) n X, and mixtures thereof, wherein n≥2, X is the residue of a coupling agent. Each block A is a poly(p-alkylstyrene) block having a molecular weight of 1-60 kg / mol, each block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / B), each block B has a molecular weight of 2-10 kg / mol, and each block C is a sulfonated polystyrene block or a polymer block consisting essentially of sulfonated styrene units and unsubstituted styrene units of the following formula (I):
[0007]
[0008] where p≥1, j≥1, k≥0, M + Selected from H + 、Na + , K +, Li + , Cs + 、Ag + , Hg + and Cu + The molecular weight of each block C is 30-80 kg / mol. The total molecular weight of the sulfonated styrene block copolymer is 65-115 kg / mol, the ion exchange capacity is 0.5-3.5 meq / g, and the glass transition temperature (Tg) is 90-200° C., measured according to ASTM 4065.
[0009] The second aspect relates to the sulfonated styrenic block copolymer being a pentablock having an ABCBA configuration represented by the structure of the following formula (II):
[0010]
[0011] Where x, y, m, n and p are independently ≥ 1, j ≥ 1, k ≥ 0, M + H + Each block A is a terminal block comprising polymerized p-methylstyrene monomers, wherein R1 is CH3. Each block B is composed of ethylene and butylene or ethylene and propylene units, and each block C is composed of sulfonated styrene units and unsubstituted styrene units.
[0012] The third aspect relates to a film comprising the sulfonated styrenic block copolymer, characterized in that it has at least a tensile stress of 6-20 MPa, a 3 The toughness is 190-1100 MPa in the dry state of Young's modulus (all the above measurements are performed according to ASTM D412), the DMA modulus at 80°C is 150-850 MPa (measured according to ASTM 4065), and the water vapor transmission rate (WVTR) in the upright state is 5-20 Kg / m 2 / day (50°C / 10%RH).
[0013] A fourth aspect relates to a lithiated-sulfonated styrenic block copolymer formed by neutralizing the sulfonated styrenic block copolymer with a 2-35 mol % aqueous solution of lithium hydroxide, wherein the membrane formed from the lithiated-sulfonated styrenic block copolymer has an ionic conductivity of >10 at 30°C. -3 S / cm (measured by electrochemical impedance spectroscopy (EIS)), and electrolyte absorption at 60°C was >25% (measured by weight gain measurement). DETAILED DESCRIPTION OF THE INVENTION
[0014] The following terms have the following meanings:
[0015] “Consisting essentially of…” means that the claimed composition mainly contains the specified material substances, and is allowed to contain additional components that do not materially affect the novel characteristics or functions of the claimed invention. If present, the content of the additional components is <30%, or <20%, or <10%.
[0016] “At least one of A, B, and C” or “any one of [A, B, and C]” refers to a single member, more than one member, or a combination of members. For example, at least one of A, B, and C includes, for example, only A, only B, or only C, as well as A and B, A and C, B and C, or A, B and C, or any other combination of A, B, and C.
[0017] Embodiments presented as "A, B, or C" should be interpreted to include only A, only B, only C, "A or B", "A or C", "B or C", or "A, B, or C".
[0018] "Any one of A, B or C" means one option among A, B or C, for example, only A, only B or only C.
[0019] “Any one of A, B, and C” means one or more options of A, B, and C, for example, only A, only B, only C, A and B, A and C, A, B, and C, etc.
[0020] As used herein, "block" refers to a portion of a polymer molecule that contains multiple identical constituent units (monomers) and has at least one compositional or configurational feature that is not present in the immediately adjacent portion (block). For example, a block copolymer having three blocks includes a block having the general structure (A) m (B) n (C)o linear and branched polymers, wherein A, B and C represent different monomers and m, n and o represent the number of repeating units in each block. (A) m and (C) o In this case they are referred to as terminal (end) blocks and may have the same or different monomer compositions and / or molar masses (expressed as the number of monomer units m and o). (B) n It is called the mid-block, and its monomer composition is similar to that of the terminal block (A). m and (C) o Different. Block (A) m (B) n and (C) oEach of the above can be composed of one or more homopolymers, random or block copolymers. The middle block can also be composed of multiple blocks, thereby producing a block copolymer with more than 3 blocks, such as a pentablock copolymer. A star block copolymer is a special form of a branched block copolymer, in which the general formula [(A) m (B) n ] p Three or more chains branch radially from a center (C), where (A) m and (B) n As defined above, p represents the number of chains, each chain being identical or different. These can also be used as block copolymers in the present disclosure. The structure of the block copolymers can be identified by GPC and proton nuclear magnetic resonance (HNMR).
[0021] "Conjugated diene" refers to an organic compound containing conjugated carbon-carbon double bonds and a total of 4-12 carbon atoms (e.g., 4-8 carbon atoms), which can be any of 1,3-butadiene and substituted butadiene, including but not limited to 1,3-cyclohexadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1-phenyl-1,3-butadiene, 1,3-pentadiene, 3-butyl-1,3-octadiene, allyl chloride, piperylene, or any combination thereof. In some embodiments, the conjugated diene block includes a mixture of butadiene and isoprene monomers. In some embodiments, 1,3-butadiene is used alone.
[0022] "Monovinyl aromatic hydrocarbons," "monoalkenyl aromatic hydrocarbons," or "vinyl aromatic hydrocarbons" refer to organic compounds containing one carbon-carbon double bond, at least one aromatic moiety, and a total of 8 to 18 carbon atoms (e.g., 8 to 12 carbon atoms). Examples include any of styrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, α-methylstyrene, vinylnaphthalene, vinyltoluene, vinylxylene, or mixtures thereof. In some embodiments, the monoalkenyl aromatic hydrocarbon block comprises substantially pure monoalkenyl aromatic hydrocarbon monomers. In some embodiments, styrene is the major component, while containing a small amount (less than 10 wt%) of a structurally related vinyl aromatic monomer, such as o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, α-methylstyrene, vinylnaphthalene, vinyltoluene, vinylxylene, or combinations thereof. In some embodiments, only styrene is used.
[0023] "Vinyl content" refers to the content of conjugated diene monomers polymerized by 1,2-addition in the case of butadiene or by 3,4-addition in the case of isoprene (thereby generating a monosubstituted olefin or vinyl group adjacent to the polymer backbone). Vinyl content can be determined by HNMR.
[0024] The "polystyrene content" or PSC of a block copolymer refers to the weight percent of vinyl aromatic (e.g., polystyrene) in the block copolymer, calculated by summing the molecular weights of all vinyl aromatic blocks divided by the total molecular weight of the block copolymer. PSC can be determined using any suitable method, such as HNMR.
[0025] "E / B" indicates polymer blocks made of ethylene and butene units in random order, formed by hydrogenation of polymerized butadiene units formed when 1,3-butadiene is polymerized by 1,2- and 1,4-addition mechanisms.
[0026] "E / P" refers to polymer blocks made of ethylene and propylene units in random order, formed by hydrogenation of polymerized isoprene units formed when isoprene is polymerized by 1,2- and 1,4-addition mechanisms.
[0027] "Coupling efficiency" is expressed as %CE, calculated using the values of wt% of coupled polymer and wt% of uncoupled polymer. The wt% of coupled polymer and uncoupled polymer are determined using the output of a differential refractometer detector. The signal intensity at a particular elution volume is proportional to the amount of material corresponding to the molecular weight of the polystyrene standard detected at that elution volume.
[0028] "Coupling agent" or "X" refers to a coupling agent commonly used in the process of preparing styrenic block copolymers SBC, for example, a silane coupling agent such as isobutyltrimethoxysilane, methyltrimethoxysilane, a polyvinyl compound, a polyvinyl aromatic hydrocarbon, a di- or polyvinyl aromatic hydrocarbon compound, a di- or polyepoxide, a di- or polyisocyanate, a di- or polyalkoxysilane, a di- or polyimine, a di- or polyaldehyde, a di- or polyketone, an alkoxytin compound, a di- or polyhalide such as a silicon halide and a halogenated silane, a mono-, di- or polyanhydride, a di- or polyester, tin tetrachloride, and tetramethylorthosilicate.
[0029] "Molecular weight" or Mw refers to the polystyrene equivalent molecular weight of a polymer block or block copolymer, in kg / mol. Mw can be determined by gel permeation chromatography (GPC) using polystyrene calibration standards, for example, according to ASTM5296-19. The GPC detector can be an ultraviolet or refractive index detector or a combination thereof. The chromatograph is calibrated using commercially available polystyrene molecular weight standards. The Mw of a polymer determined using a GPC so calibrated is the polystyrene equivalent molecular weight or apparent molecular weight. The Mw shown herein is measured at the peak of the GPC trace, commonly referred to as the polystyrene equivalent "peak molecular weight", expressed as M p。
[0030] An "electrochemical cell" is a "rechargeable battery" or "battery cell" comprising a positive electrode, a negative electrode, and an electrolyte in direct contact therebetween, wherein the electrolyte conducts ions (e.g., Na + Mg 2+ , Li + , K + ), but the positive electrode and the negative electrode are electrically isolated. In some embodiments, the rechargeable battery can include multiple positive electrodes and / or multiple negative electrodes in one container.
[0031] "Membrane" refers to a continuous, flexible sheet or layer of material (film or coating, etc.) that acts as a selective barrier, thereby allowing substances such as molecules, ions, gases or particles to pass through, but preventing other substances from passing through.
[0032] "Ion exchange capacity" or IEC refers to the total active sites or functional groups in a polymer that are responsible for ion exchange. Acid-base titration can be used to determine IEC, see "International Journal of Hydrogen Energy", Vol. 39, No. 10, March 26, 2014, pp. 5054-5062, "Determination of the ion exchange capacity of anion selective membranes". IEC is the reciprocal of "equivalent weight" or EW, where equivalent weight or EW is the weight of polymer required to provide 1 mole of exchangeable protons.
[0033] "Battery" refers to an energy storage system or energy device, and "lithium-ion battery" as used herein also includes batteries based on materials other than lithium (such as sodium, potassium, etc.) used in energy storage systems.
[0034] "Suspension-prone" means that a polymer, polymer block, compound, monomer, oligomer, etc. is susceptible, sensitive or capable of reacting with a sulfur-containing compound (e.g., SO3, H2SO4, etc.) under conditions commonly used for sulfonation, wherein sulfonation is likely to occur to obtain a sulfonated product. In some embodiments, the degree of sulfonation of the "suspension-prone" polymer block after sulfonation is >10 mol%, or >20 mol%, or >30 mol%, or >50 mol%, or >75 mol% of the total polymer block, i.e., the polymer block has >10 mol%, or >20 mol%, or >30 mol%, or >50 mol%, or >75 mol% of sulfonic acid or sulfonate functional groups.
[0035] "Sulfonation resistant" means that each block is almost not sulfonated under the conditions usually used for sulfonation, and the content of sulfonic acid or sulfonate functional groups in the block is <10 mol%, or <8 mol%, or <5 mol%.
[0036] "Dry" or "dry state (dry state)" refers to or describes the hydration state of a material or film that absorbs substantially no water or absorbs a small amount of water. For example, a material or film that is only in contact with the atmosphere is considered to be in a dry state.
[0037] "Water" refers to deionized water, tap water, distilled water, processed water, natural water, spring water, mineral water, sparkling water, hard water, or mixtures thereof.
[0038] The present invention relates to a separator for an energy storage device, comprising, consisting essentially of, or consisting of a functionalized styrenic block copolymer in the form of a lithiated-sulfonated hydrogenated styrenic block copolymer (Li-SSBC). The copolymer is prepared by sulfonating an SBC precursor to obtain a sulfonated styrenic block copolymer (SSBC) and then reacting the styrenic block copolymer with Li + ions are obtained by neutralizing the ionic blocks of SSBC (thereby changing its properties for use as a separator in energy storage devices).
[0039] Styrenic Block Copolymer (SBC) Precursor: The membrane includes a functionalized styrenic block copolymer obtained from an SBC precursor. The SBC precursor is any one of a linear, branched, and radial block copolymer having at least one terminal block A and at least one internal block B and C.
[0040] Sulfonated styrenic block copolymers (SBC) have any of the following structures: triblock, tetrablock, pentablock and coupled structures. SBC precursors are essentially composed of polymer blocks A, B and C and have the following general configurations: ACBA, ACBCA, ABCBA, (ACB) n A. (ABC) n A, (ACB) n X, (ABC) n X, and mixtures thereof, wherein n≥2, and X is the residue of a coupling agent. Blocks A, B and C are defined in the following paragraphs.
[0041] Each block A is derived from a para-substituted vinyl aromatic monomer, wherein the para-substituted group is C1-C 12Straight chain or branched alkyl. In some embodiments, block A is a para-substituted styrene monomer selected from the following: p-methylstyrene, p-ethylstyrene, p-n-propylstyrene, p-isopropylstyrene, p-n-butylstyrene, p-sec-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, isomers of p-decylstyrene, isomers of p-dodecylstyrene, and mixtures of the above monomers. Examples of para-substituted styrene monomers include p-tert-butylstyrene and p-methylstyrene, of which p-tert-butylstyrene is the most preferred. The monomer can be a mixture of monomers, depending on the specific source. Compared with other polymer blocks in SBC, block A has a relatively high glass transition temperature, for example greater than 50°C, which can give the copolymer ideal mechanical properties and other functional properties, including morphology, which makes them suitable for use as dielectric materials. In some embodiments, the peak molecular weight of block A is 1-60kg / mol, or 2-50kg / mol, or 5-40kg / mol, or 8-25kg / mol.
[0042] In some embodiments, block A comprises 30-80 wt%, or 35-75 wt%, or 40-70 wt%, or 45-65 wt%, based on the total weight of the SBC precursor.
[0043] Block B includes a hydrogenated polymer or copolymer of a conjugated diene derived from any one of isoprene, butadiene, and mixtures thereof. After hydrogenation, each isoprene unit (if present) is converted into an ethylene-propylene (EP) block, and each butadiene unit (if present) is converted into an ethylene-butylene (EB) block. In some embodiments, the peak molecular weight of block B is 1-25 kg / mol, or 1-20 kg / mol, or 1-10 kg / mol, or 1-9 kg / mol, or 5-8 kg / mol, or >1 kg / mol, or <25 kg / mol, or <22 kg / mol, or <18 kg / mol, or <15 kg / mol, or <12 kg / mol, or <10 kg / mol, or >2 kg / mol.
[0044] In some embodiments, block B is sufficiently hydrogenated so that the precursor SBC and subsequent SSBC (after sulfonation) have a conjugated diene block of ≤0.15 meq / g, or <0.10 meq / g, or <0.05 meq / g, or <0.03 meq / g, or >0.0001 meq / g. The level of hydrogenation in the final SSBC product and hydrogenated diene polymer can be determined by UV-VIS spectrophotometry and / or 1H NMR.
[0045] In some embodiments, the vinyl content of polymer block B before hydrogenation is 8-85 wt%, or >15 wt%, or <50 wt%, or 20-75 wt%, or 30-50 wt%, based on the total weight of polymerized conjugated dienes in polymer block B. The vinyl content can be measured by 1H NMR before or after hydrogenation.
[0046] In some embodiments, block B comprises ≤ 25, or 5-25, or 10-25, or 15-25, or 5-20, or 5-15, or 5-20 wt % based on the total weight of the SBC precursor.
[0047] In some embodiments, block C comprises one or more segments of polymerized vinyl aromatic monomers selected from unsubstituted styrene monomers.Block C is susceptible to sulfonation, and comprises 40-60 wt%, or 45-55 wt%, or 40-50 wt%, based on the total weight of the SBC precursor.
[0048] In some embodiments, the peak molecular weight of block C is 30-80 kg / mol, or 35-60 kg / mol, or 40-60 kg / mol, or 40-50 kg / mol.
[0049] Sulfonated styrenic block copolymer (SSBC): SSBC is obtained by sulfonating the above-mentioned styrenic block polymer (SBC) precursor. SSBC has at least one sulfonic acid group, such as -SO3, which can be in acid form (e.g., -SO3H, sulfonic acid) or salt form (e.g., -SO3Na). In some embodiments, the sulfonic acid group is in the form of a metal salt, an ammonium salt, or an amine salt.
[0050] In some embodiments, the SSBC is characterized as being fully sulfonated, meaning having >10 mol% sulfonic acid or sulfonate functional groups (degree of sulfonation) based on the total moles of monomer units or polymer blocks to be sulfonated. In some embodiments, the degree of sulfonation of the SSBC is 1-100 mol%, or at least 10 mol%, or >15, or >20, or >25, or >30, or >40, or >50, or >60, or >70, or >80, or >90, or >99 mol%. The degree of sulfonation can be measured by NMR.
[0051] In some embodiments, the sulfonated styrenic block copolymer (SSBC) has any of the following structures: triblock, tetrablock, pentablock, and coupled structures. The SSBC has the following general configuration: ACBA, ACBCA, ABCBA, (ACB) n A. (ABC) n A, (ACB) n X, (ABC)n X, and mixtures thereof, wherein n≥2, X is the residue of a coupling agent. At least one block is susceptible to sulfonation or is susceptible to the introduction of acid groups to improve other functionalizations of hydrophilicity. In some embodiments, blocks A and B are resistant to sulfonation, and block C is susceptible to sulfonation. In some embodiments, each block A is a poly(p-alkylstyrene) block, and each block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / C). In some embodiments, each block C is a sulfonated polystyrene block or a polymer block consisting essentially of sulfonated styrene units and unsubstituted styrene units of the following formula (I):
[0052]
[0053] where p≥1, j≥1, k≥0, M + Selected from H + 、Na + , k + , Li + , Cs + 、Ag + , Hg + and Cu + .
[0054] As used herein, sulfonated styrenic block copolymers SSBC refer to styrenic block copolymers having M=H + block copolymers, and by making sulfonated styrene block copolymers (having M=H + ) reacts with an ionizable metal compound to obtain a metal salt (i.e., Na + , K + , Li + , Cs + 、Ag + , Hg + and Cu + ) and further neutralized (metallized) sulfonated styrenic block copolymers.
[0055] In some embodiments, each block A is a poly(p-alkylstyrene) derived from a p-alkylstyrene monomer selected from the group consisting of p-methylstyrene, p-ethylstyrene, p-n-propylstyrene, p-isopropylstyrene, p-n-butylstyrene, p-sec-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, isomers of p-decylstyrene, isomers of p-dodecylstyrene, and mixtures thereof.
[0056] In some embodiments, block B is a hydrogenated polybutadiene block, wherein prior to hydrogenation, the polybutadiene block is derived from a conjugated diene monomer selected from the group consisting of butadiene, 2,3-dimethyl-1,3-butadiene, 1-phenyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 3-butyl-1,3-octadiene, and mixtures thereof.
[0057] In some embodiments, the SSBC is a pentablock having an ABCBA configuration represented by the structure of Formula (II):
[0058]
[0059] where x, y, m, n and p are each independently ≥ 1, j ≥ 1, and k ≥ 0, m + H + Each block A is a terminal block comprising polymerized p-methylstyrene monomers, wherein R1 is CH3. Each block B is composed of ethylene and butylene or ethylene and propylene units, and each block C is composed of sulfonated styrene units and unsubstituted styrene units.
[0060] In some embodiments, the peak molecular weight of the SSBC is 20-250 kg / mol, or 25-225 kg / mol, or 30-200 kg / mol, or 45-175 kg / mol, or 55-150 kg / mol, or 65-120 kg / mol, or >20 kg / mol, or <250 kg / mol.
[0061] In some embodiments, the block B content of the SSBC is <30%, or <28%, or <24%, or <20%, or <15%, or >3%, or 5-20%, based on the total weight of the pentablock copolymer.
[0062] In some embodiments, block C is susceptible to sulfonation and comprises 40-65 wt%, or 45-55 wt%, or 40-50 wt%, based on the total weight of the pentablock copolymer.
[0063] In some embodiments, the weight ratio of block A to block B is 10:1-1:2, or 5:1-1:2, or 4:1-3:1, or 2:1-1:1.
[0064] In some embodiments, the ratio of sulfonated styrene units to unsubstituted styrene units in block C is 99:1-1:99 mol%, or 99.5:0.5-0.5:99.5 mol%, or 98:2-2:98 mol%, or 95:5-5:95 mol%, or 92:8-8:92 mol%, or 90:10-10:90 mol%.
[0065] In some embodiments, the SSBC has a coupled structure of (ACB)2X, (ABC)2X configuration with a coupling efficiency of 50-85%, or 55-80%, or >50%, or <85%.
[0066] It should be noted that in addition to the sulfonated SBC precursors described herein to obtain SSBC, other polymers containing sulfonic acid groups may also be used. Examples include perfluorosulfonic acid polymers (e.g., sulfonated tetrafluoroethylene), sulfonated polyolefins, sulfonated polyimides, sulfonated polyamides, sulfonated polyesters, polystyrene sulfonates, sulfonated styrenic block copolymers, sulfonated polysulfones (e.g., polyethersulfones), sulfonated polyketones (e.g., polyetheretherketones), sulfonated polyphenylene oxides, and mixtures thereof.
[0067] Neutralization of Sulfonated Styrenic Block Copolymers: In some embodiments, the sulfonic acid functional groups in block C of the SSBC are "neutralized" by reacting the sulfonated block polymer with an ionizable metal compound to obtain a metal salt.
[0068] In some embodiments, suitable metal ions for forming the neutralized SSBC are positively charged ions of metals, preferably monovalent, divalent, and trivalent ions of metals in Groups IA, IB, IIA, IIIB, IIIA, IIIB, and VIII of the IUPAC Periodic Table. These metal ions may be complexed or non-complexed and may be used alone or in any mixture thereof. Suitable monovalent metal ions are Na + , K + , Li + , Cs + 、Ag + , Hg + and Cu + A suitable divalent metal ion is Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , Cu 2+ 、Cd 2+ Sn 2+ , Pb 2+ , Fe 2+ 、Co 2+ 、Ni 2+ and Zn 2+ A suitable trivalent metal ion is Al 3+ Sc 3+ , Fe 3+ ,La 3+ and Y 3+Preferred compounds are hydroxides, oxides, alkoxides, carboxylates, formates, acetates, methoxides, ethoxides, nitrates, carbonates and bicarbonates of the above metal ions. + Can be used interchangeably as Na + .
[0069] In some embodiments, the neutralization reaction is carried out by (i) adding the metal compound directly or in a solvent to a solution of the functionalized block copolymer, followed by neutralization, precipitation and separation of the resulting polymer, or (ii) melt blending the functionalized block copolymer with the metal compound. Melt blending is preferably carried out at an elevated temperature to promote uniform distribution of the metal compound and volatilize the neutralized product.
[0070] The degree of functionalization and neutralization can be measured by known techniques, such as infrared analysis or elemental analysis to determine overall functionality, and titration with a strong base to determine functionality and / or neutralization (metal salt content).
[0071] In some embodiments, the SSBC is neutralized with 2-35 mol%, or >2 mol%, or >5 mol%, or >10 mol%, or >15 mol%, or >20 mol%, or <35 mol% of a concentrated aqueous solution of lithium hydroxide.
[0072] In some embodiments, SSBC (pentablock) is neutralized with lithium hydroxide to form a neutralized SSBC (Li-SSBC) of the following formula (III):
[0073]
[0074] R1 is CH3, x, y, m, n and p≥1, j≥1, k≥0, M + For Li + .
[0075] In some embodiments, the number of groups constituting "j" in block C is 30-100 mol% (of block C), and the remainder is groups constituting "k". Block A is a poly(p-methylstyrene) block, block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / C), and block C is a lithiated-sulfonated polystyrene block, or a polymer block consisting essentially of lithiated-sulfonated styrene units and styrene units.
[0076] In some embodiments, the degree of lithiation-sulfonation (LiSO3) in the neutralized lithiated-sulfonated hydrogenated styrenic block copolymer (Li-SSBC) is 30-100 mol%, or >25 mol%, or >30 mol%, or >35 mol%, or >45 mol%, or >60 mol%, or >75 mol%, or >85 mol%, or >95 mol%.
[0077] Crosslinking agent: A crosslinking agent is a reactive compound, such as a monomer, oligomer or polymer, selected from acrylates, compounds having at least two vinyl groups, isocyanurates, polyisocyanates (aliphatic and / or aromatic), diisocyanates, polyester diols (aliphatic and / or aromatic), silanes (such as alkoxy or vinyl silanes), siloxanes, polyether-modified siloxanes, thiols, compounds having two or more isopropenyl groups, anhydrides, and mixtures thereof.
[0078] In some embodiments, the crosslinking agent is selected from polymers / oligomers containing at least two vinyl groups. Such crosslinking agents include styrene-butadiene copolymers, polybutadiene, styrene-butadiene-divinylbenzene copolymers, etc. The oligomers have at least two vinyl groups and are formed from monomers such as styrene, α-methylstyrene, vinyltoluene, p-methylstyrene, ethylvinylbenzene, vinylnaphthalene, and mixtures thereof.
[0079] In some embodiments, the crosslinking agent is an aliphatic polyisocyanate or an aliphatic polyester diol.
[0080] In some embodiments, the content of the crosslinking agent is 0.1-15, or 0.5-12, or 1-10, or 2-8, 0.5-5 wt %, based on the total weight of the copolymer.
[0081] Optional Additives: In embodiments where the Li-SSBC is used as a separator, the composition further comprises an additive selected from the group consisting of activators, curing agents, crosslinking agents (other than diamine-based), stabilizers, neutralizers, thickeners, coalescing agents, slip agents, mold release agents, antiozonants, color changing pH indicators, tackifiers, film forming additives, dyes, pigments, UV stabilizers, UV absorbers, fillers, other resins, redox pairs, flame retardants, viscosity modifiers, wetting agents, degassing agents, toughening agents, colorants, heat stabilizers, light stabilizers, lubricants, flow modifiers, anti-drip agents, anti-caking agents, antistatic agents, processing aids, stress relief additives, adhesives, and mixtures thereof.
[0082] In some embodiments, the composition further comprises a polymer other than the alkyl halide substituted SBC.
[0083] In some embodiments, the composition further comprises at least one plasticizer, a high dielectric constant solvent or a liquid electrolyte to promote the increase of ionic conductivity. Examples of plasticizers include di(2-ethylhexyl) phthalate (BEHP), dibutyl phthalate (DBP), diisobutyl phthalate (DIBP) or a mixture thereof. In some embodiments, the liquid electrolyte is selected from propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC) or a mixture thereof. In some embodiments, the liquid electrolyte is formed by dissolving the electrolyte (i.e., a lithium salt, such as LiPF6, LiBF4, LiClO4, LiTFSI) in a high dielectric constant solvent before adding the lithiated-sulfonated block copolymer.
[0084] In some embodiments, the additive is used in an amount of up to 10 wt%, or 0.1-10 wt%, or 0.5-5 wt%, or 1-10 wt%, or 1-5 wt%, based on the total weight of the lithiated-sulfonated block copolymer composition.
[0085] Films or membranes containing SSBC / Li-SSBC: Depending on the end use, films or membranes containing SSBC or Li-SSBC copolymers can be formed. The film can be formed by known methods, such as casting, electrospinning, extrusion, compression, coating, such as dipping, flow coating, roller coating, rod coating, spray coating, curtain, gravure printing, brush coating, wire wound rod coating, disk reverse roll coating, roller gap coating, spray coating, knife coating, spin coating, dip coating, slot die coating or ultrasonic spray coating. In some embodiments, the film is a free-standing film or supported on a substrate, such as glass, plastic, ceramic, porcelain, etc.
[0086] In some embodiments, the thin film is formed directly on the electrode of the energy storage device by the known methods described above. In the case of lithium-ion batteries, the thin film can be formed directly on the cathode or anode. Examples include cathodes made of lithium nickel manganese cobalt oxide (LiNiMnCoO2), lithium iron phosphate (LiFePO4), and anodes made of graphite, silicon-containing graphite, and lithium metal, etc.
[0087] In some embodiments, the film is made by solvent casting. Examples of solvents include n-hexane, cyclohexane, dichloromethane, vinyl chloride, isopropanol, acetone, N,N-dimethylacetamide, 1-methyl-2-pyrrolidone, 1,3-dioxolane, 2-methoxyethanol, dimethylformamide, benzyl alcohol, toluene, xylene, dimethyl sulfoxide, and mixtures thereof. The film is then dried from room temperature to 80°C, or 30-70°C, or 35-65°C, with or without vacuum, in a continuous or batch process.
[0088] In some embodiments, the film has a thickness of 0.1-50 μm, or 1-45 μm, or 5-40 μm, or 8-25 μm, or 10-30 μm, or 12-25 μm, or >0.1 μm, or <50 μm.
[0089] Crosslinking or curing by heat / radiation treatment: Depending on the application, the articles (e.g., films or membranes, etc.) obtained from the composition containing the SSBC are crosslinked by neutralization, ion complexation, or by curing using heat or radiation treatment. The crosslinking can be achieved by heat, UV radiation, gamma radiation, electron beam or microwave, with or without thermal or photoinitiators.
[0090] In some embodiments, crosslinking or curing of the film is carried out in the presence of a thermal initiator at a temperature of 40-200°C, or 45-180°C, or 50-150°C, or 55-120°C, or 60-100°C, or >45°C or <140°C, for a period of 1-240 minutes, or 2-220 minutes, or 5-200 minutes, or 10-150 minutes, or 15-100 minutes, or 20-60 minutes, or >2 minutes or <60 minutes.
[0091] In some embodiments, crosslinking or curing of the film is performed by exposing the film to an electron beam or gamma radiation at a radiation dose of 10-250 kGy (kilogray), or 20-220 kGy, or 30-200 kGy, or 40-180 kGy, or 50-160 kGy, or 60-150 kGy, or >20 kGy or <220 kGy. Electron beam treatment can be achieved with an electron accelerator, such as any of an electrostatic direct current (DC), an electric DC, a radio frequency (RF) linear accelerator (LINACS), a magnetic induction LINAC, and a continuous wave (CW) machine.
[0092] In some embodiments, the sample or film before or after crosslinking or curing is treated with a solvent annealing step. Solvent annealing of the film can be achieved by placing the film in a closed chamber with a solvent reservoir for 1-96 hours, or 2-72 hours, or 5-48 hours, or 12-40 hours, or>10 hours. In some embodiments, the solvent is sprayed directly on the film for 2 seconds to 1 minute, or 5-40 seconds, or 10-30 seconds, or>2 seconds to cover the film sample with the solvent. The solvent can be any polar solvent, such as water, hexafluoroisopropanol, trifluoroethanol, ethylene glycol, methanol, ethanol, acetic acid, benzyl alcohol, 2-propanol, and mixtures thereof.
[0093] In some embodiments, the film has a thickness of 1-400 μm, or 2-200 μm, or 5-100 μm, or 10-50 μm, or 0.1-50 μm, or 1-45 μm, or >0.1 μm, or <40 μm.
[0094] In some embodiments, the film is heat laminated, solvent laminated or adhesive laminated to a microporous carrier (substrate) for use in a water purification system. Non-limiting examples of microporous carrier substrates include polyester, polyethylene, polypropylene, polymethylpentene (PMP), polyethylene terephthalate, cellulose, cellulose nitrate, cellulose acetate, nylon, polytetrafluoroethylene, fiber braids or nonwoven materials, etc. Alternatively, the membrane can be supported on a commercially available membrane.
[0095] Performance of SSBC: The membrane or film comprising, consisting essentially of, or consisting of SSBC is characterized by selective permeability, ion exchange capacity (IEC) performance, ionic conductivity, and excellent liquid electrolyte absorption characteristics. The membrane / film also undergoes considerable expansion upon absorption of liquid electrolyte, for example, at least 10-250%, or 25-250%, or >10%, or 35-225%, or 50-200%, or 75-175%, or <250% as measured by weight gain measurement at ambient temperature.
[0096] In some embodiments, the IEC of the SSBC is >0.5 meq / g, or >0.75 meq / g, or >1 meq / g, or >1.25 meq / g, or >2.2 meq / g, or >2.5 meq / g, or >4.0 meq / g, or <4.0 meq / g, or 1.5-3.5 meq / g, as measured by acid-base titration. In some embodiments, the lower ion exchange capacity membranes (1.0 meq / g) are believed to be more stable than the higher ion exchange capacity membranes (1.5 and 2.0 meq / g).
[0097] In some embodiments, the SSBC has a glass transition temperature (Tg) of 90-200°C, or 90-180°C, or 95-180°C, or >90°C, or >95°C, or <200°C as measured by dynamic mechanical analysis (DMA) according to ASTM 4065.
[0098] In some embodiments, the film composed of SSBC is characterized by having sufficient thickness to make nanostructured materials for membrane compositions, for example, the thickness of the film for porous membranes or composite materials is at least 0.1 μm, or 0.25 μm, or 0.75 μm, or 1 μm, or <1 μm, and the thickness of the composite substrate is 1-30 μm, or 3-25 μm, or 8-20 μm, or >1 μm, or <50 μm. In some embodiments, the thickness of the membrane is 1-150 μm, or 3-100 μm, or 5-75 μm, or 8-65 μm.
[0099] The mechanical properties of the films (dry state) containing SSBC were measured according to ASTM D412 standard and are as follows.
[0100] In some embodiments, the tensile strength of the film is 5-30, or 5-18, or 7-15, or 7.5-14, or 8-12, or >5, or <15 MPa, and the tensile strength measured after 1 day (24 hours) is 3-10, or 3.5-8, or 4-7.5, or 4.5-7, or >3.5, or <8 MPa.
[0101] In some embodiments, the toughness of the film is 3-25, or 3.2-22, or 3.5-20, or 3.8-18, or 4-15, or 4.2-12, or 4.5-10, or >3.5, or <15 MJ / m 3 .
[0102] In some embodiments, the film has a Young's modulus of 190-1100, or 175-1000, or 190-950, or 300-900, or 340-860, or 400-750, or >100, or <1100 MPa.
[0103] In some embodiments, the film has a modulus of 150-850 MPa, or 185-760 MPa, or 240-700 MPa, or 300-640 MPa, or >150 MPa, or <850 MPa at 80°C as measured by dynamic mechanical analysis (DMA) according to ASTM 4065.
[0104] In some embodiments, the swelling ratio of the membrane in water after 24 hours at room temperature is <70%, or <90%, or <100%, or <120%, or <150%, or <200%, or <250%, or 3-70%, or 5-100%, or 8-200%, or 40-300%, or 50-250%, or 60-220, or 70-200%, or 80-180%, or 100-160%, based on the total initial weight of the membrane.
[0105] In some embodiments, the vertical WVTR of the film is 1000-30000, or 5000-28000, or 6000-25000, or 7000-22000, or 8000-20000, or 9000-18000, or >3000, or <25000 g / m 2 In some embodiments, the film has an inverted WVTR of 1000-150000, or 5000-140000, or 8000-120000, or 15000-100000, or 20000-80000, or >15000, or <125000 g / m 2 / day. WVTR measurement is carried out in accordance with ASTM E96 / E96M at 50°C and 10% humidity in an upright or inverted manner.
[0106] In some embodiments, the durability of the film in accelerated aging is up to 30 days, or > 5 days, or > 7 days, or < 14 days, or < 30 days, measured in water at 80°C.
[0107] In some embodiments, films containing cross-linked SSBCs have a % KCl permselectivity (10:1 molar ratio) at room temperature of >40%, or <100%, or 40-100%, or 45-95%, or 55-90%, or 65-85%.
[0108] Performance of Li-SSBC: After the introduction of Li + After ion neutralization, the membrane or film comprising, consisting essentially of, or consisting of Li-SSBC is characterized by selective permeability, having ion exchange capacity (IEC) performance, ionic conductivity (neat polymer and saturated with liquid electrolyte), liquid electrolyte absorption, electronic conductivity, thermal stability, Li interfacial stability, lithium ion transference number, and excellent liquid electrolyte absorption characteristics. When the membrane / film absorbs liquid electrolyte, it will also experience considerable expansion, for example, at least 25-250%, or >25%, or 35-225%, or 50-200%, or 75-175%, or <250% as measured by weight gain measurement at ambient temperature.
[0109] In some embodiments, the IEC of the film is >0.5 meq / g, or >0.75 meq / g, or >1 meq / g, or >1.25 meq / g, or >1.5 meq / g, or >2.2 meq / g, or >2.5 meq / g, or >4.0 meq / g, or <4.0 meq / g, or 1.0-6 meq / g as measured by acid-base titration.
[0110] In some embodiments, the ionic conductivity of the film (pure polymer) is >10 at 30°C. -9 S / cm, or 1.50x10 -9 –2.0x10 -4 , or 2.0x10 -9 -1.0x10 -4 , or 8.0x10 -8 –9.0x10 -5 , or 6.0x10 -8 -9.0x10 -5 , or 5.0x10 -8 -8.5x10 -5 , or 2.5x10 -6 –1.0x10 -3 , or 5.0x10 -6 – 1.5x10 -3 , or 1.0x10 -5 –2.0x10 -3 or >2.0x10 -6 , or >4.0x10 -6 S / cm.
[0111] In some embodiments, the ionic conductivity of the film (polymer saturated with solvent) is >10 at 30°C as measured by electrochemical impedance spectroscopy (EIS). -9 S / cm, or 1.50x10 -9 –2.0x10 -4 , or 2.0x10 -9 -1.0x10 -4 , or 8.0x10 -8 –9.0x10 -5 , or 6.0x10 -8 -9.0x10 -5 or 5.0x10 -8 -8.5x10 -5 , 2.5x10 -6 –1.0x10 -3 , or 5.0x10 -6 – 1.5x10 -3 , or 1.0x10 -5 –2.0x10 -3 or >2.0x10 -6 , or >4.0x10 -6 S / cm.
[0112] In some embodiments, the film has a carbonate solvent (ethylene carbonate, dimethyl carbonate, etc.) liquid electrolyte absorption rate of 25-250%, or >25%, or 35-225%, or 50-200%, or 75-175%, or <250% at ambient temperature.
[0113] In some embodiments, the film is thermally stable with a weight loss of <5%, or <4%, or <2.5%, or <1%, as measured by thermogravimetric analysis (20°C to 200°C at a heating rate of 10°C / min, isothermal TGA at 15°C for 8 hours).
[0114] In some embodiments, the Li interface stability of the film is <10%, or <8%, or <6.5%, or <5%, or <4%, or <2% (i.e., less than 10% change after 100 cycles at 25°C and 60°C) as measured by lithium symmetric cell-electrochemical impedance spectroscopy as a function of time and temperature after activation cycles.
[0115] In some embodiments, the film has a lithium ion transference number of >0.4, or >0.5, or >0.6, or >0.8, or 0.4-1.0 according to the Bruce-Vincent method using a lithium symmetric cell.
[0116] Applications: In some embodiments, SSBC and Li-SSBC products can be used as flakes, solutions, or particles for end-use applications in addition to being used as films or membranes.
[0117] In some embodiments, the lithiated-sulfonated block copolymer (Li-SSBC) is used as a component of an energy storage device, such as in any of a current collector, an electrode, or a separator (as a binder). In some embodiments, the lithiated-sulfonated block copolymer is coated or deposited on a substrate comprising a polyolefin (porous separator). In other embodiments, the block copolymer layer is coated on at least one side of the separator. In other embodiments, both sides of the separator are coated with the same or different lithiated-sulfonated block copolymer compositions. Example
[0118] The following examples are not limiting.
[0119] Viscoelastic behavior was measured by DMA according to ASTM 4065.
[0120] Mechanical properties in dry state including toughness, Young's modulus, tensile strength and elongation at break were measured according to ASTM D412.
[0121] The water vapor transmission rate (WVTR) measurements of the samples were performed according to ASTM E96 / E96M.
[0122] The degree of sulfonation of the samples was determined by potentiometric titration.
[0123] Ionic conductivity was measured by electrochemical impedance spectroscopy (EIS), where an impedance analyzer was combined with a potentiostat / galvanostat. 2 A circular polyelectrolyte composition film sample was placed between two stainless steel solid blocking electrodes encapsulated by a Teflon holder. For temperature-dependent ionic conductivity measurements, heat from 20 to 100°C was applied to the stainless steel blocking electrode by a heating tape. Impedance spectra were collected in the frequency range of 1 MHz to 0.1 Hz over a temperature range of 30 to 100°C at an open circuit potential under an AC (alternating current) perturbation of 10 mV. The film was kept at each temperature for 1 hour to reach equilibrium, and then five measurements were performed at equilibrium. The ionic conductivity was calculated by using the following equation: σ = L / (AR), where L is the thickness of the film and A is the cross-sectional area of the blocking electrode (approximately 1.2161 cm 2 ), R is the resistance of the film determined by equivalent circuit regression of the Nyquist data.
[0124] The liquid electrolyte (LE) absorption of polymer (SSBC / Celgard) membranes or films is estimated by measuring the weight of the membrane sheet immersed in liquid electrolyte using the following formula:
[0125] Absorption rate % = (W t –W o ) / W o x 100
[0126] Where W t and W o are the weights of the membrane soaked with liquid electrolyte and the dry sheet of the porous membrane without liquid electrolyte, respectively.
[0127] Example 1 (SSBC-1 comparison)
[0128] The structure of the sulfonated pentablock copolymer (SSBC-1) is poly[tert-butylstyrene-b-(ethylene-al t-propylene)-b-(styrene-co-styrene-sulfonate)-b-(ethylene-alt-propylene)-tert-butylstyrene] (tBS-EP-sPS-EP-tBS). The Mp of the tBS block is 15 kg / mol, the Mp of each EP block is 10 kg / mol, and the Mp of the internal sPS block is 28 kg / mol. At 10.5 wt% solids content in a 1:1 (cyclohexane / heptane) non-polar solvent mixture, SSBC-1 has an IEC of 2.0 mmol / g, a molecular weight of 78 kg / mol, a glass transition temperature of 86°C, and an upright WVTR (50°C / 10% relative humidity) of 7.5 kg / m 2 / sky.
[0129] Example 2 (SSBC-2)
[0130] The structure of the sulfonated pentablock copolymer SSBC-2 is poly[p-methylstyrene-b-(ethylene-al t-propylene)-b-(styrene-co-styrene-sulfonate)-b-(ethylene-al t-propylene)-p-methylstyrene] (pMS-EP-sPS-EP-pMS). The Mp of the pMS block is 15 kg / mol, the Mp of each EP block is 7 kg / mol, and the Mp of the internal sPS block is 42 kg / mol. At 10.5 wt% solid content in a 1:1 (cyclohexane / heptane) non-polar solvent mixture, SSBC-2 has an IEC of 2.0 mmol / g, a molecular weight of 86 kg / mol, a glass transition temperature of 98°C, and an upright WVTR (50°C / 10% relative humidity) of 9.5 kg / m 2 / sky.
[0131] Table 1 shows the mechanical properties of Examples 1 and 2 in the dry state.
[0132] Table 1
[0133]
[0134] Example 3
[0135] SSBC-2 polymer (about 0.1 g) was dissolved in 50 ml of toluene / methanol (90 / 10, v / v) solution. Nitrogen was bubbled through the solution for 30 minutes to remove dissolved CO2 from the sample. The resulting polymer solution was then treated with an excess (about 10 mol%) of lithium hydroxide in concentrated aqueous solution. The product sulfonate of SBC (Li-SSBC) was used to prepare a film as described in Example 4.
[0136] Example 4
[0137] Thin films were prepared by first dissolving the SO3LiSBC (Li-SSBC) of Example 3 in either pure tetrahydrofuran (SBC-x-THF) or a 85 / 15 v / v toluene / isopropanol mixture (SBC-x-TIPA) to produce a 2 wt% solution. The solvent dielectric constant (κ) was used to assess the polarity differences between the casting solvents used: κ THF =7.43 and κ TIPA = 4.91. The thickness of the film obtained by solution casting followed by solvent evaporation was about 20 μm, the thickness of the substrate (composite) was 20 μm, and the SO3LiSBC coating was 0.5 μm. These films were used for further processing / testing.
[0138] Some films were cast in Teflon molds, covered to limit the solvent evaporation rate, and dried for 48 hours. Some of the resulting films were solvent vapor annealed in THF for 24 hours and then vacuum dried at 60°C for 24-48 hours. After drying, the films were immersed in electrolyte solutions for further characterization.
[0139] Table 2 reports the results of the ionic conductivity of the film after neutralization with 1M LiOH solution for 24 hours, and the electrolyte absorption results when the film samples were immersed in the electrolyte solution (1M LiPF6 in *EC / DEC v / v=1 / 1) at 25°C for different immersion times. As shown below, the electrolyte absorption depends on the immersion time, and the ionic conductivity depends on the electrolyte absorption. Wherein, *EC / DEC refers to ethylene carbonate, diethyl carbonate, and v / v refers to the volume ratio.
[0140] Table 2
[0141]
[0142] Although the terms "including" and "comprising" are used herein to describe various aspects, the terms "consisting essentially of" and "consisting of" may be substituted for "including" to provide more specific aspects of the present disclosure and are also disclosed.
Claims
1. A sulfonated styrenic block copolymer having a general configuration selected from the group consisting of: ACBA, ACBC-A, ABCB-A, (ACB) n A. (ABC) n A. (ACB) n X, (ABC) n X and mixtures thereof, wherein: n≥2, X is the residue of a coupling agent, Each block A is a poly(p-alkylstyrene) block having a peak molecular weight of 1-60 kg / mol, Each block B is a hydrogenated polyisoprene block (E / P) or a hydrogenated polybutadiene block (E / C), and the peak molecular weight of each block B is 1-10 kg / mol, Each block C is a sulfonated polystyrene block or a polymer block consisting essentially of sulfonated styrene units and unsubstituted styrene units of the following formula (I): Where p≥l, j≥l, k≥0, M + Selected from H + 、Na + , K + , Li + , Cs + 、Ag + , Hg + and Cu + , the peak molecular weight of each block C is 30-80 kg / mol; and The sulfonated styrene block copolymer has the following properties: The total molecular weight is 65-115 kg / mol, Ion exchange capacity of 0.5-3.5 meq / g, and The glass transition temperature Tg is 90-200°C, measured according to ASTM 4065.
2. The sulfonated styrenic block copolymer according to claim 1, wherein the sulfonated styrenic block copolymer is a pentablock having an ABCBA configuration represented by the structure of the following formula (II): Where x, y, m, n and p are independently ≥ 1, j ≥ 1, k ≥ 0, M + Yes H + ,and Each block A is a terminal block comprising polymerized p-methylstyrene monomer, wherein R1 is CH3, Each block B consists of ethylene and butene or ethylene and propylene units, and Each block C is composed of sulfonated styrene units and unsubstituted styrene units.
3. A film comprising the sulfonated styrenic block copolymer of claim 2, wherein the film is characterized by having at least one of the following properties: The tensile stress is 6-20MPa, Toughness is 3-25MJ / m 3 , The Young's modulus in dry state is 190-1100 MPa. All the above measurements are carried out according to ASTM D412 standard. Modulus at 80°C of 150-850 MPa, measured according to ASTM 4065, and The water vapor transmission rate in the vertical mode is 5-20kg / m 2 / day, measured at 50°C and 10% relative humidity.
4. The sulfonated styrenic block copolymer according to claim 1, wherein the sulfonated styrenic block copolymer is a pentablock having an ABCBA configuration represented by the structure of the following formula (III): Where x, y, m, n and p are independently ≥ 1, j ≥ 1, k ≥ 0, M + It's Li + ,and Each block A is a terminal block comprising polymerized p-methylstyrene monomer, wherein R1 is CH3, Each block B consists of ethylene and butene or ethylene and propylene units, and Each block C is composed of sulfonated styrene units and unsubstituted styrene units.
5. A lithiated-sulfonated styrenic block copolymer formed by neutralizing the sulfonated styrenic block copolymer of claim 2 with a 2-35 mol % aqueous lithium hydroxide solution, wherein a membrane formed from the lithiated-sulfonated styrenic block copolymer has the following properties: The ionic conductivity at 30°C is >10 -3 S / cm, measured by electrochemical impedance spectroscopy, and The electrolyte absorption at 60°C was >25% as measured by weight gain measurement.
6. A film comprising the sulfonated styrenic block copolymer according to any one of claims 1 to 2.
7. The sulfonated styrene block copolymer according to any one of claims 1, 2, 4-5, wherein the weight ratio of block A to block B in the sulfonated styrene block copolymer is 10:1-1:
2.
8. The sulfonated styrenic block copolymer according to any one of claims 1, 2, 4-5, wherein block C accounts for 40-65 wt% of the sulfonated styrenic block copolymer.
9. The sulfonated styrenic block copolymer of claim 1 wherein the poly(p-alkylstyrene) is derived from a p-alkylstyrene monomer selected from the group consisting of p-methylstyrene, p-ethylstyrene, p-n-propylstyrene, p-isopropylstyrene, p-n-butylstyrene, p-sec-butylstyrene, p-isobutylstyrene, p-tert-butylstyrene, isomers of p-decylstyrene, isomers of p-dodecylstyrene, and mixtures thereof.
10. The sulfonated styrenic block copolymer of claim 1, wherein the block B is a hydrogenated polybutadiene block, wherein prior to hydrogenation, the polybutadiene block is derived from a conjugated diene monomer selected from the group consisting of butadiene, 2,3-dimethyl-1,3-butadiene, 1-phenyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 3-butyl-1,3-octadiene, and mixtures thereof.
11. A solid polymer electrolyte for an energy storage device, wherein the electrolyte is formed by adding a sufficient amount of a liquid electrolyte to the film of claim 6 and maintaining it for a sufficient time to allow the film to swell by at least 10% by volume, wherein the liquid electrolyte comprises a lithium salt dissolved in a solvent, the lithium salt being selected from LiPF6, LiBF4, LiClO4, LiTFSI, and mixtures thereof, and the solvent being selected from propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and mixtures thereof.
12. A separator for an energy storage device, wherein the separator is formed by applying the lithiated-sulfonated styrenic block copolymer of any one of claims 4 to 5 to a substrate comprising a polyolefin to form a coating, wherein the polyolefin is selected from modified polyolefins, polyethylene, polypropylene, polymethylpentene, and mixtures thereof, and wherein the thickness of the substrate is 3-100 μm. 13 . The separator according to claim 12 , wherein the lithiated-sulfonated styrenic block copolymer coating has a thickness of 0.1-25 μm. An energy storage device comprising the diaphragm according to claim 12 .
15. An energy storage device comprising the film according to claim 3.
Citation Information
Cited By
Composite binder, preparation method thereof and application of composite binder in negative electrode of all-solid-state lithium ion battery
CN120383893A